Effects of head and tail as swinging appendages on the dynamic walking performance of a quadruped robot. Issue 12 (14th March 2016) - Zhang, Xiuli; Gong, Jiaqing; Yao, Yanan
SUMMARY: We designed a quadruped robot with a one-degree-of-freedom (1-DOF)-pitch head, a 1-DOF-roll tail, and 14 active DOFs in total, which are controlled via a central pattern generator (CPG) based on a Hopf oscillator. Head and tail movements are coupled to the leg movements with fixed phase differences. Experiments show that tail swinging in roll can equilibrate feet–ground reaction forces (GRF), reducing yaw errors and enabling the robot to maintain its direction when trotting. Head swing in pitch has the potential to increase flight time and stride length of the swinging legs and increase the robot's forward velocity when running in bounds.